Transgenerational changes in pod maturation phenology and seed traits of Glycine soja infested by the bean bug Riptortus pedestris - Adachi-Fukunaga, Shuhei; Nakabayashi, Yui; Tokuda, Makoto (PLOS ONE, 2022)
Land plants have diverse defenses against herbivores. In some cases, plant response to insect herbivory may be chronological and even transgenerational. Feeding by various stink bugs, such as the bean bug Riptortus pedestris (Hemiptera: Alydidae), induce physiological changes in soybean, called as green stem syndrome, which are characterized by delayed senescence in stems, leaves, and pods. To investigate the plant response to the bean bug feeding in the infested generation and its offspring, we studied the effects of R. pedestris infestation on Glycine soja, the ancestral wild species of soybean. Field surveys revealed that the occurrence of the autumn R. pedestris generation coincided with G. soja pod maturation in both lowland and mountainous sites. Following infestation by R. pedestris, pod maturation was significantly delayed in G. soja. When G. soja seeds obtained from infested and non-infested plants were cultivated, the progeny of infested plants exhibited much earlier pod maturation and larger-sized seed production than that of control plants, indicating that R. pedestris feeding induced transgenerational changes. Because earlier seed maturity results in asynchrony with occurrence of R. pedestris, the transgenerational changes in plant phenology are considered to be an adaptive transgenerational and chronological defense for the plant against feeding by the stink bug.